2001
DOI: 10.1016/s0896-6273(01)00523-2
|View full text |Cite|
|
Sign up to set email alerts
|

Deficient Neurogenesis in Forebrain-Specific Presenilin-1 Knockout Mice Is Associated with Reduced Clearance of Hippocampal Memory Traces

Abstract: To examine the in vivo function of presenilin-1 (PS1), we selectively deleted the PS1 gene in excitatory neurons of the adult mouse forebrain. These conditional knockout mice were viable and grew normally, but they exhibited a pronounced deficiency in enrichment-induced neurogenesis in the dentate gyrus. This reduction in neurogenesis did not result in appreciable learning deficits, indicating that addition of new neurons is not required for memory formation. However, our postlearning enrichment experiments le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
248
4
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 433 publications
(280 citation statements)
references
References 62 publications
26
248
4
2
Order By: Relevance
“…Our data on exercise and memory retention seem to contradict those of Feng et al (2001), who stated that hippocampal neurogenesis might serve to remove outdated information from the hippocampus. Feng and coworkers reported that an increase in neurogenesis after acquisition of a learning task impairs memory retention, whereas we see an improvement.…”
Section: Exercise Promotes Hippocampal Neurogenesiscontrasting
confidence: 99%
“…Our data on exercise and memory retention seem to contradict those of Feng et al (2001), who stated that hippocampal neurogenesis might serve to remove outdated information from the hippocampus. Feng and coworkers reported that an increase in neurogenesis after acquisition of a learning task impairs memory retention, whereas we see an improvement.…”
Section: Exercise Promotes Hippocampal Neurogenesiscontrasting
confidence: 99%
“…This will not be an easy task, since the region of origin of the new CA1 neurons is not unequivocally shown. A nonselective inhibition of neurogenesis by mitotic inhibitors or irradiation will not be sufficient to solve the issue, since such treatment is known to impair learning and memory also in nonischemic animals, possibly through inhibition of neurogenesis in the subgranular zone (Feng et al, 2001;Raber et al, 2004;Shors et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, 1 h/d of EE was sufficient to attenuate deficits in spatial learning in the MWM following FP (Fig. 6), and 3 h/d of EE produced increases in neurogenesis and improvements in memory and learning in intact mice [18] and rats [7]. Even shorter durations, as little as 40 min/d, was sufficient to produce alterations in mRNA and brain weight in developing animals [13].…”
Section: Discussionmentioning
confidence: 94%
“…First, specific pathogen free (SPF) guidelines and space restrictions of our animal vivarium prevented us from housing animals in EE on a continuous basis. Second, whereas most previous studies have used continuous housing in an enriched environment, there have been a few reports demonstrating that short daily periods of EE, ranging from 45 min to 3 hours per day [13,18], could produce alterations in the brain. Third, shorter periods of EE may be more translatable to certain clinical situations than continuous EE.…”
Section: Environmental Enrichmentmentioning
confidence: 99%